The Masquerade as Experiment: Gender and Representation in Mercedes Cabello de Carbonera's "El Conspirador. Autobiografia de un hombre público." - Mathews, Cristina (Hispanic Review)
This article discusses the representation in the novel "El Conspirador. Autobiografía de un hombre pùblico," by Peruvian author Mercedes Cabello de Carbonera. It explains the major parts of the novel and the reasonings for Cabello's decision to write a male autobiography.